2003
DOI: 10.1046/j.1365-4362.42.s1.6.x
|View full text |Cite
|
Sign up to set email alerts
|

Ciclopirox gel in the treatment of patients with interdigital tinea pedis

Abstract: Ciclopirox gel 0.77% applied twice daily for 4 weeks is an effective treatment of moderate interdigital tinea pedis due to T. rubrum, T. mentagrophytes and E. floccosum and is associated with a low incidence of minor adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 6 publications
(8 reference statements)
0
27
0
Order By: Relevance
“…Ciclopiroxolamine (1% and 0·77%) used for 4 weeks was evaluated in two placebo‐controlled trials ( n = 144 30 and n = 317 14 ). A statistically significant relative reduction in treatment failure was observed (RR 0·27, 95% CI 0·11–0·66).…”
Section: Resultsmentioning
confidence: 99%
“…Ciclopiroxolamine (1% and 0·77%) used for 4 weeks was evaluated in two placebo‐controlled trials ( n = 144 30 and n = 317 14 ). A statistically significant relative reduction in treatment failure was observed (RR 0·27, 95% CI 0·11–0·66).…”
Section: Resultsmentioning
confidence: 99%
“…The unique mechanism of action of ciclopirox, combined with its antibacterial and anti‐inflammatory properties, make it an ideal candidate for the treatment of superficial dermatophyte and yeast infections. This is evidenced by its success in the treatment of interdigital tinea pedis, which often presents as dermatophyte fungus with superimposed bacterial infection and inflammation 1,2 . Seborrheic dermatitis also may involve a combination of fungal infection and inflammatory action, 21 which has been successfully controlled using ciclopirox 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the potential for resistance of organisms to ciclopirox may be lower than for other antifungals 7 . Thus ciclopirox has been used in multiple clinical trials for a wide variety of indications, and years of clinical usage have demonstrated the safety and efficacy of ciclopirox in the treatment of superficial mycoses 1,2,6,11,17,20,22–24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Posology of the drugs was based on the previous studies and recommended frequency of use (3,4). The diagnosis of tinea pedis was based on the clinical findings and positive potassium hydroxide (KOH) examination.…”
Section: Methodsmentioning
confidence: 99%